Analysis of molecular signaling partways regulating HB-EGF- induced mitotic cell division and neurogenesis in the zebrafish olfactory epithelium - Şireci, Şiran. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
The zebrafish olfactory epithelium (OE) has an outstanding regenerative capacity among other nervous tissues. Two distinct modes of neurogenesis regulate the mechanism of olfactory sensory neuron (OSN) generation under physiological and injury conditions. Continuous division and differentiation of globose basal cells (GBCs) provide the lifelong turnover and maintenance of OSNs, whereas repair neurogenesis is achieved by the activation of horizontal basal cells (HBCs) to replenish the loss of OSNs following acute injury. Transcriptome analysis and in situ-hybridization of the injured OE showed a strong upregulation of the signaling factor heparin-binding epidermal growth factor-like growth factor (HB-EGF) shortly after damage. Previously, exogenous administration of recombinant HB-EGF to the OE was shown to increase proliferative activity in HBCs and the generation of OSNs. Inhibition of HB-EGF ectodomain shedding showed the opposite effect and reduced cell proliferation in response to injury. These findings suggested a critical role for HB-EGF during regeneration of the zebrafish OE. The work presented in this study further validates that HB- EGF is a key regulator of OSN neurogenesis in the zebrafish OE. Pharmacological inhibition of HB-EGF ectodomain shedding reduced OSN regeneration as well as cell proliferation. Similarly, direct inhibition of soluble HB-EGF suppressed HBC proliferation following injury and impaired OSN regeneration. The analysis of hbegfa and ascl1a expression by in situ- hybridization upon HB-EGF stimulation also showed direct activation of HBCs, which proliferate and give rise to neurons through the transient induction of intermediate GBC populations. In addition, the potential role of Leptin and IL- 11 cytokines on cell proliferation and a possible synergism between HB-EGF and these cytokines were investigated. Exogenous stimulation with recombinant cytokines separately or in combination with HB-EGF did not point out an effect on cell proliferation. NOTE Keywords : Cellular pathways, Olfactory epithelium, Regeneration, Zebrafish, Signaling pathways.
Keywords: Olfactory mucosa.; Epithelium.; Zebra danio.